Pemikiran Nyai Nur Rofiah Dalam Buku Nalar Kritis Muslimah dan Relevansinya Terhadap Kekerasan Verbal Anak Usia Dini - Herlega Oktaria; Fatrica Syafri; Ixsir Eliya (Insititut Agama Islam Negeri (IAIN) Curup, 2022)
The problem raised in this study is the concept of Nyai Nur Rofiah's thinking and aims to know the thoughts of Nyai Nur Rofiah in the book Muslimah's Critical Reason for early childhood verbal violence. This research uses a type of research, namely library research. The technique of data collection is collecting literature. The data used comes from primary data as well as secondary data. The results of the study can be concluded that Nyai Nur Rofiah's thoughts in the book of muslimah's critical reason about women and gender are important for humans to know the differences between men and women that are distinguished by two things, namely gender and gender. In research that researchers examine the influence of parents on child development is very large. Because children aged 0-8 years are very wide of behavior that is not good. Because at that age children really like to model something done by the environment and both parents. Therefore, parents must always give good love and appreciation to their children. Therefore, from the explanation that researchers understand from this book, it has relevance to verbal violence in early childhood.